Impact of Age on Outcome of Rifapentine-Based Weekly Therapy for Latent Tuberculosis Infection. (19th November 2020) - Huang, Hung-Ling; Lee, Meng-Rui; Cheng, Meng-Hsuan; Lu, Po-Liang; Huang, Chun-Kai; Sheu, Chau-Chyun; Lai, Ping-Chang; Chen, Tun-Chieh; Wang, Jann-Yuan; Chong, Inn-Wen
Abstract: Background: Weekly rifapentine and isoniazid (3HP) is gaining popularity for latent tuberculosis infection treatment because of its short course and high completion rate. Prior to widespread use, comprehensive 3HP treatment assessment covering an all-age population is essential. Methods: Participants receiving ≥1 3HP dose from September 2014 to December 2019 were stratified into elderly (≥65 years), middle-aged (>35 & <65 years), and younger (≤35 years) age groups. This study investigated the impact of age on treatment outcome, particularly systemic drug reactions (SDRs) and 3HP discontinuation. Results: Overall, 134 of 579 (23.1%) participants were elderly. The completion rate was 83.1% overall and was highest and lowest in the younger group (94.5%) and elderly (73.9%) group, respectively. However, the 3HP discontinuation rate was not significantly different among the 3 groups in multivariate logistic regression analysis. In total, 362 (62.5%) participants experienced 1 or more adverse drug reactions (ADRs), of which 38 (10.5%) and 98 (27.1%) required temporary and permanent treatment interruption, respectively. The SDR risk was 11.2% in overall and 17.1% in the middle-aged group, 3.04-fold higher than that in the elderly group ( P = .025). This finding was consistently observed in different clinical settings. Hypertensive events accompanied with flu-like symptoms occurred in 11.2% of elderly participants, and accounted for 50% of grade ≥3 ADRs. Conclusions: With proper medical support and programmatic follow-up, the 3HP completion rate is >70% even in elderly participants. In middle-aged and elderly individuals, 3HP should be employed with caution because of risk of SDRs and hypertensive events, respectively. Summary: Under programmatic medical support, widespread use of weekly rifapentine and isoniazid (3HP) for latent tuberculosis treatment is possible for its high completion rate. 3HP should be employed with caution for risk of systemic drug reactions and hypertensive events in middle-aged and elderly individuals, respectively.